Ruwahan Tradition among NU Communities of Javanese and Betawi Ethnic Groups Prior to Ramadan - Ahmad Sholahuddin Yusuf (Lakpesdam PCNU Kota Salatiga, 2023)
Ruwahan is a living religious tradition maintained within Nahdlatul Ulama (NU) communities in Indonesia, particularly among Javanese and Betawi Muslims, as part of spiritual preparation prior to Ramadan. The tradition is analytically important because it illuminates the dynamic interplay between Islamic teachings, local culture, and social change. This study examines (1) how ruwahan is practiced in NU communities in Java and Betawi settings, (2) the meanings constructed around the ritual, and (3) the ways the tradition is transformed in contemporary social contexts. Employing a qualitative approach, the research draws on participant observation and in-depth interviews with community leaders, NU administrators, and residents involved in ruwahan observances. Data were analyzed using thematic analysis informed by cultural anthropology and the sociology of religion. The findings suggest that while ritual forms differ between Javanese and Betawi NU communities, they converge in substantive meanings: ruwahan functions as a medium for praying for ancestors, strengthening social cohesion, and internalizing Islamic values through culturally embedded practice. In the context of modernization and urbanization, ruwahan has undergone changes in format and implementation; nevertheless, it remains sustained through adaptive strategies and ongoing negotiations of meaning. The study concludes that ruwahan constitutes a dynamic, contextual expression of Islam Nusantara in contemporary Indonesian society.